Characterizing the diversity in users' perceptions - Karapanos, Evangelos; Martens, Jean Bernard O.S. (My University, 2007)
This paper proposes a novel approach to modeling the diversity in users' perceptions, based on a mixture of qualitative and quantitative techniques: the Repertory Grid Technique and Multi-Dimensional Scaling. The proposed method can be used for identifying diverse user groups that can inspire a range of personas, or for selecting subjects for field studies and usability tests. In a case study we explored the perceptions of product creators and end users towards an innovative product in its early design stage.
Keywords: Multi-dimensional scaling; Repertory grid; User profiling